The Influence of Capital Structure, Liquidity, and Company Size on Sulselbar Bank's Profitability - Goso Goso (Enrichment : Journal of Management, 2022)
The purpose of this study is to analyze and determine the effect of the capital structure is measured using financial ratios, specifically the debt-to-equity ratio (DER). Liquidity, or often known as working capital ratio, is measured through current assets (current ratio), and company size is seen from the total assets owned by the company, which can be used to carry out company operations, against profitability to assess the company's ability to make a profit in a certain period by using Return on Investment, Return on Assets, Profit Margin, and Return on Equity. Secondary data is used from the financial statements of Sulselbar bank for the period 2017–2021. Data analysis techniques use multiple linear regression with the help of SPSS 24. The results and findings of the research show that the capital structure proxied by DER and DAR has no effect on the profitability of Sulselbar Bank, while liquidity proxied with Current Ratio, Quick Ratio, and Cash Ratio partially has a significant effect on profitability, while the size of the company proxied with Ln Total Assets partially has no effect on the profitability of Sulselbar Bank proxied with ROA, ROI, and ROE. The capital structure, liquidity, and company size together affect the profitability of Sulselbar bank. The predictor variable is able to explain the model with an adjusted R Square value of 50%, while the remaining 50% is explained by factors that are not included in this study model.